HUBUNGAN INISIASI MENYUSUI DINI DENGAN HIPERBILIRUBINEMIA PADA NEONATUS : Literature Review - Miftahul Jannah (2020)
Hyperbilirubinemia is a clinical physiological condition that occurs in newborns. Hyperbilirubinemia can be prevented by initiating early breastfeeding. The purpose of this literature review is to make a literature analysis related to the initiation of early breastfeeding with hyperbilirubinemia in neonates systematically. This review literature was taken from a database (Scopus, Scientific Journal Rankings, Science direct, Ebsco, and Pubmed) using English in the last 5 years. The search terms included in the keywords are "neonates", "Early Initiation of Breastfeeding" and "hyperbilirubinemia". The initial study search results from the entire database used were obtained as many as 708 studies and filtered two stages based on the PICO formula and CRAAP method. A total of 13 studies were selected for analysis. ABO incompatibility factors, parity, gestational age, birth weight <2500 grams, pregnancy hypertension, gestational diabetes mellitus, can cause hyperbilirubinemia. Early breastfeeding initiation has a relationship with hyperbilirubinemia in newborns. Early detection of symptoms of hyperbilirubinemia and the implementation of early breastfeeding are very important to prevent the incidence of hyperbilirubinemia in neonates. Keywords : Hyperbilirubinemia, early breastfeeding initiation, neonates